Japan's Financial Markets: The Lost Decade - Beate Reszat (Hamburg Institute of International Economics (HWWA), 2003)
Recent debates about the state of Japan's financial system focus on the weakness of Japanese banks. But, in the complex financial relations of an advanced economy bank finance cannot be seen separate from other forms of financial intermediation. Despite the reform efforts under the Big Bang program, financial markets in Japan show severe signs of malfunctioning, distortion and backwardness. The paper gives an overview of the current state of markets for money, bonds, equities and derivatives arguing that for reform to become successful measures to develop an entirely different market culture were needed. It calls for a redefinition of the role of interest groups in the financial intermediation process – including the role of government.
Keywords: E58; E62; G10; N25; 330; Finanzmarkt; Finanzintermediär; Finanzsektor; Wirtschaftliche Instabilität; Bankenreform; Japan